Formation processes of methane-derived authigenic carbonates from the Gulf of Cadiz - Magalhães, Vitor H. (2019)
The Gulf of Cadiz, NE Atlantic, represents an area of extensive formation of methane-derived authigenic carbonates (MDAC), indicative of fluid seepage. These MDAC, that reach extraordinary length and thickness, were geophysically mapped and sampled and the recovered carbonate-cemented material has δ13C values as low as − 56.2‰ VPDB, indicating methane as the major carbon source. The MDAC form two main lithologic groups, one mainly comprising dolomite and the second dominated by aragonite. The dolomite-dominated samples were found along fault-controlled diapiric ridges, on some mud volcanoes and mud diapirs, all on the pathway of the Mediterranean Outflow Water, and along fault scarps. Aragonite pavements were found associated with mud volcanoes and along fault scarps, but are otherwise not restricted to the pathways of the Mediterranean Outflow Water. Based on the results from this study, we propose that the two lithologic groups reflect different geochemical formation environments associated with a formation model based on their morphology, mineralogy and geochemistry. The aragonite-dominated samples represent precipitation of authigenic carbonates at the sediment–seawater interface or close to it, in a high alkalinity environment resulting from anaerobic oxidation of methane-rich fluids venting into sulphate-bearing porewaters. In contrast, the dolomite-dominated samples result from cementation along fluid conduits inside the sedimentary column with a somewhat restricted seawater ventilation. The dolomite chimneys form in places presently swept by the strong flow of the Mediterranean undercurrent so that the unconsolidated sediments are eroded and the chimneys are exposed at the seafloor. The widespread and large abundance of MDAC is a direct evidence of extensive methane seepage episodes in the Gulf of Cadiz. The coincidence of the different lithologic types in close spatial and temporal association indicates a persistence of seepage episodes in some structures over large periods of time.